Anand Patwardhan's Chronicles of Socio-political Realities. Issue 2 (December 2016) - Patwardhan, Anand
Probably India's best-known documentary film-maker Anand Patwardhan, for close to four decades now, has been raking the country's political consciousness through his films, which delve into the crux of India's social and political lives. In this piece, the editors have put together, with Patwardhan's permission, his writings from his blog (http://patwardhan.com/wp/ ) on the state atrocities upon Dalits in Maharashtra, the protests through poems and songs by a young group of Dalit activists from Pune—the Kabir Kala Manch (KKM)—and the satyagraha for the freedom of expression by its leaders like Sheetal Sathe; on the Supreme Court judgment that failed the Narmada Bachao Andolan as well as the belief in the justice system, making irrelevant a whole body of evidence built by the Andolan over the years that underlined the huge financial and human costs of the Sardar Sarovar dam project; and on the whole climate of intolerance that was behind the attack on M. F. Husain for his depiction of Hindu goddess Saraswati. This piece also includes a commentary by Alex Napier on Patwardhan's documentary of the Narmada Bachao Andolan, drawn from Patwardhan's blog.  These are important social commentaries of our times.